Digital Marketing Drives MSME Sales Growth in Indonesia: Pemasaran Digital Dorong Pertumbuhan Penjualan UMKM di Indonesia - Sulistiyowati, Elik; Rahmawati , Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of marketplace effectiveness, social media use, and promotional activities on the sales of Micro, Small, and Medium Enterprises (MSMEs) in Sidoarjo District. Using primary data from 67 MSME actors selected through simple random sampling, we applied descriptive statistical analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, and t-tests with SPSS version 26. The findings reveal that effective marketplace utilization, strategic social media use, and targeted promotions significantly enhance MSME sales. These insights suggest that MSMEs should leverage digital tools and strategic marketing to improve their sales performance. Highlights: 1. Marketplaces and social media boost MSME sales.2. Proper promotions increase sales performance.3. Digital tools are essential for MSME growth. Keywords: MSMEs, marketplace effectiveness, social media, promotion, sales growth